Nutritional Characterization of Leaf Powder of Introduced Moringa oleifera Lam. Genotypes in the Lower Shiwalik Hills of the Western Himalays, India - Attri, Varun; Vijay kumar (Indian Journal of Agroforestry, 2025)
Moringa oleifera Lam., commonly known as the drumstick or miracle tree, is recognized for its exceptional nutritional and medicinal potential. In this study, six genotypes viz.,PKM1, PKM2, Jodhpur Local, Odisse Local, Mandya Local, and PM1 (Punjab Local) were evaluated under a completely randomized block design with three replications. Leaves were harvested green, shade dried, milled into powder, and analyzed for proximate composition, vitamin content, and macro and micronutrients. Dry matter content ranged from 18.20 ± 0.92 % (PKM 2) to 21.00 ± 1.61 % (Jodhpur Local), and ash content varied between 11.47 ± 0.31 % (Jodhpur Local) and 14.47 ± 0.31 % (PKM 2). Crude protein content was highest in PKM 1 (27.71 ± 2.01 %) and lowest in PM 1 (18.75 ± 2.72 %), while crude fiber ranged from 13.57 ± 1.47 % (PKM 1) to 16.20 ± 0.71 % (Jodhpur Local). The vitamin profile showed considerable variation, with PKM 1 exhibiting the highest values for Vitamin A (16.00 ± 0.50 mg100 g-1), Vitamin B1 (2.62 ± 0.02 mg100 g-1), Vitamin B2 (21.33 ± 0.76 mg100 g-1), Vitamin B3 (8.47 ± 0.31 mg 100 g-1), Vitamin C (17.63 ± 0.67 mg 100 g-1), and Vitamin E (115.33 ± 2.52 mg 100 g-1). Macronutrient content varied notably across genotypes: calcium was highest in PKM 1 (26.33 ± 1.53 mg100 g-1), phosphorus in PM 1 (3.06 ± 0.053 mg 100 g-1), potassium in PM 1 (19.71 ± 0.63 mg100 g-1), magnesium in PM 1 (4.44 ± 0.082 mg100 g-1, sodium in Odisse Local (0.75 ± 0.029 mg 100 g-1), and sulphur in PKM 2 (16.33 ± 0.10 mg 100 g-1). Micronutrient analysis revealed maximum manganese in PKM 1 (51.81 ± 1.89 mg kg-1), zinc in PM 1 (32.11 ± 1.15 mg kg-1), copper in PM 1 (15.15 ± 0.76 mg kg-1), iron in Jodhpur Local (395.67 ± 11.68 mg kg-1), and boron in PKM 1 (52.25 ± 0.87 mg kg-1). These findings demonstrate significant genotypic variation in the nutritional composition of Moringa oleifera Lam., with PKM 1, PKM 2, PM 1, and Jodhpur Local identified as promising candidates for nutritional enhancement and health-based applications.